2016
DOI: 10.1002/ep.12353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical activation of fly ash on the properties of geopolymers investigated by XPS method

Abstract: Geopolymer materials are obtained by the alkaline activation of alumina-silicate sources, the best of which is metakaolin. The aim of this work is to develop methods for working properties prediction of geopolymer materials based on the starting materials-not only metakaolin. The formation of geopolymers from four types of fly ash samples (FA) from Slovakia derived from various combustion processes was investigated. Chemical bond changes during mechanical activation were examined by X-ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In addition to Si-O and Si-O 2 , there remains a peak at a high binding energy for FA-1 and FA-2. According to the standard binding energy spectrum, it was found that this peak can be assigned to SiO 2 gel, which was also reported by Kanuchova [8,33].…”
Section: Xpssupporting
confidence: 78%
See 2 more Smart Citations
“…In addition to Si-O and Si-O 2 , there remains a peak at a high binding energy for FA-1 and FA-2. According to the standard binding energy spectrum, it was found that this peak can be assigned to SiO 2 gel, which was also reported by Kanuchova [8,33].…”
Section: Xpssupporting
confidence: 78%
“…Fly ash can be considered as the world's fifth largest raw material resource [7]. Currently, one possible utilization of fly ash is in the synthesis of alkali-activated materials named geopolymers [8,9]. PC fly ash can successfully be used for the manufacturing of cement, building materials concrete, and concrete-admixed products [10], as it is categorized as a pozzolan, while CFB fly ash with a higher carbon content is broadly used as an insulator and adsorbent [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, strong vibration milling not only weakens microstructure of certain components and enhance their reactivity, but also may lead to the formation of new aluminosilicate bonds between aluminate and silicate constituents of the fly ash as it caused more microstructural changes. Kanuchova et al [26] have observed an increase in binding energy with the appearance of new specifications for Al and Si atoms by XPS method in mechanically activated fly ash. Such changes of the binding energy indicate the appearance of new Al-O-Si bonds.…”
Section: Geopolymers Prepared From Fly Ashes Activated With Various Mmentioning
confidence: 99%
“…In Slovakia, almost all of the heating plant waste, especially fly ash, is not utilized. It can be concluded that little attention is paid to this issue in Slovakia, which is reflected in the lack of evidence-based practices [40]. In this paper, the utilization of fly ash from Slovakia, mainly deposited in a heap, which creates an environmental problem, was used as a potential aluminosilicate material for the geopolymerization process.…”
Section: Introductionmentioning
confidence: 99%